Gamal (Gliricidia Sepium) Leaf Extract Increase Mortality of Fasciola gigantica In Vitro - Zulianti, Brillia; Hamid, Iwan Sahrial; Yudhana, Aditya; Rahmahani, Jola; Yunita, Maya Nurwartanti; Wibawati, Prima Ayu (Jurnal Medik Veteriner, 2021)
Fasciolosis is a disease caused by infection with liver fluke (Fasciola sp). Fasciolosis is a parasitic disease that is important because it can cause high economic losses. The aim of this study was to investigate the effect of gamal (Gliricidia sepium) leaf extract against mortality of Fasciola gigantica in vitro study. In present study was completely randomized design with six treatments and each treatment were divided into four replications. A total of 240 specimens from infected cattles were used in this study. The observation and recording of F. gigantica mortality in all treatments with concentrations of gamal leaf extract P1 (1%), P2 (2%), P3 (3), P4 (4%), K + (Nitroxynil 2%) and K- (physiological NaCl) rate was done in 30, 60, 90, 120, 150, 180, 210 and 240 minutes, respectively. The mortality of F. gigantica was confirmed if there was no movement when triggered by anatomy tweezers then dipped in slightly warm water (50 15í¢„Æ’"> ). The data was analyzed using ANAVA Faktorial and continued with Duncan Multiple Range Test. The results of this study were shown the lowest and the highest mortality rate recorded at minutes 30 and 240 respectively. Moreover, the mean of mortality rate were peaked in nitroxynil (K+) and 1% gamal leaf extract treatment, while the lowest mean of mortality rate occurs in NaCl (K-) treatment. Present study conclude that gamal leaf extract has anthelmintic effect on the mortality rate of Fasciola gigantica. Gamal leaf extract with 1% concentration was claimed to be the most effective.